Ecological Losses in Cases of Environmental Damage Due to Mining Business Activities - Ruth Marthania Silaban (Dinasti Research, 2024)
The reclamation after mining business activities provides concrete evidence of how should the management of ecological losses received by the environment due to environmental damage, which is often only from the aspect of economic value. But further than that actually, the ecological loss itself is how about restoring the environment that has been damaged. The calculation of reclamation also only calculates from an economic point of descriptive analytical method with a normative juridical approach. Based on the results of the first study, ecological losses generally only focus on how to compensate for the loss in economic value. Whereas further than that, the regulation of the calculation of ecological losses is environmental recovery which requires a longer time than just post-mining reclamation on an economic side only, but instruments in environmental law such as administrative instruments are needed as a preventive measure against ecological losses, civil as the responsibility of business actors, to criminal acts as a form of compliance in order to achieve law enforcement. Second, in applying the regulation in the field, legal practitioners do not define ecological loss”in the same voice. There are different interpretations that ecological losses in the perspective of law are that enforces define completely and equally that ecological losses are not only assessed from the financing of compensation.